The outcome of treatment of Trans-Atlantic Inter-Society Consensus D aortoiliac disease - Maisa A Abdel Wahab; Ola I Saleh (Wolters Kluwer Medknow Publications, 2018)
Objective The long-term durability of the open bypass is better than that of endovascular treatment (EVT) for Trans-Atlantic Inter-Society Consensus (TASC) D aortoiliac lesions, but many recently developed devices and a variety of access options have increased the success rates of EVT, with less operative mortality and complication rates. In this study, we aimed to compare the technical success rates, primary patency rate, clinical outcomes, and complication for TASC D aortoiliac lesions treated by endovascular and surgical procedures. Patients and methods Data from 89 patients with chronic iliac artery stenosis and/or occlusion who were treated with endovascular or surgical treatment were retrospectively reviewed in the period between January 2003 and December 2017. Results The procedure time was longer for the surgical group than for the EVT group. The total complication rate was higher in the surgical group than in the EVT group. The mortality rate associated higher with the surgical group. There was no statistically significant difference between the groups regarding 2-year primary patency rates. Conclusion This study revealed that patients with severe aortoiliac occlusive disease (TASC D) can be treated with EVT or surgically with satisfactory results, with better technical success in the surgical group than in the EVT group. Furthermore, the 2-year patency rate for both groups was acceptable.